2016
DOI: 10.1103/physrevb.93.155401
|View full text |Cite
|
Sign up to set email alerts
|

Semi-infinite jellium: Step potential model

Abstract: The surface energy, the one-particle distribution function of electrons, etc. of a semi-bounded metal within the framework of the semi-infinite jellium are calculated. The influence of the potential barrier height on these characteristics is studied. The barrier height is found from the condition of the minimum of the surface energy. The surface energy is positive in the entire domain of the Wigner-Seitz radius of metals, and it is in sufficiently good agreement with experimental data.PACS numbers: 73.20.-r; 7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…[52][53][54][55][56]. Consequently, the following expression for the thermodynamic potential Ω (4.2) can be obtained,…”
Section: Functional Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…[52][53][54][55][56]. Consequently, the following expression for the thermodynamic potential Ω (4.2) can be obtained,…”
Section: Functional Representationmentioning
confidence: 99%
“…An effective potential of inter-electron interaction, which we have studied recently in [52][53][54][55][56], is crucial for calculating of the general expression for thermodynamic potential. It is shown that within certain approximations the thermodynamic potential can be represented as a functional of the one-and twoparticle distribution functions of electrons.…”
Section: Introductionmentioning
confidence: 99%
“…where two possible orientations of the electron spin are taken into account and transition from the sum over two-dimensional vector k || to the integral is performed according to Refs. [17,18]. We assume that the concentration of the positive charge ̺ 0 is equal to the bulk concentration of electrons 3e/(4πr 3 s ), where r s is the Wigner-Seitz radius.…”
Section: Modelmentioning
confidence: 99%
“…We extract from the Hamiltonian (1) a Hamiltonian of the semi-infinite jellium model H jell [4][5][6], which is used as a basic system for the study of thermodynamic and structural properties of semibounded metal. As a result, we get that…”
Section: Modelmentioning
confidence: 99%